Berberine as a new neuraminidase inhibitor drug: A systematic review - Majid Asadi-Samani; Dhiya Altememy; Javad Saffari-Chaleshtor; Mohammad-Taghi Moradi (Shahrekord University of Medical Sciences, 2024)
Influenza neuraminidase (NA) plays a main role in the viral replication of the influenza virus. It has been considered one of the targets for anti-influenza drugs. Anti-influenza drugs such as zanamivir, oseltamivir, and peramivir can fight the virus via the inhibition of NA. However, due to adverse reactions, the resistance of the viral strains and sudden changes in NA inhibitors, the identification of novel inhibitors is needed. Nature products such as berberine have been reported against influenza. In this systematic review, we have focused on the anti-influenza effects of berberine and its main role in the inhibition of NA of the virus. For this aim, "Berberine" was searched with "Influenza" or "flu" or "common cold" or "neuraminidase" in Web of Science, PubMed, Scopus, and Google Scholar databases from 1990 to April 2023. Studies have demonstrated that berberine and its derivatives have a wide range of biological effects such as antiviral effects against viruses like herpes simplex virus, human cytomegalovirus, and influenza A virus. The present study indicates that berberine and some of its derivatives are able to inhibit the influenza virus through NA blockade. Berberine is able to superimpose into the allosteric binding site and shows reversible non-competitive behavior in the ligand-receptor interaction for the inhibition of NA.